Relationship between perineal wound care, abstainment to eating culture and personal hygiene using feminine hygiene (binahong leaf, betel green mint leaf) with perineum wound healing long time - Lea Ingne Reffita; Rohemah Rohemah (Institute of Computer Science (IOCS), 2023)
The puerperium lasts from six weeks to six weeks after delivery. The first delivery often results in a perineal tear. Perineal wounds require special care as without proper care, the risk of infection increases. Age, nutritional status, perineal wound care, personal hygiene, medication, tradition, knowledge, environment, socioeconomics and staff handling are factors that influence perineal wound healing. This study aims to determine the relationship between perineal wound care, food restrictions, and personal hygiene using Personal Hygiene with perineal wound healing time in independent midwife practices. The study used analytic observation of case control/retrospective design. The population was postpartum women from the third day to the seventh day after early labor. Non-random, or non-probability, sampling was used in the consecutive or quota sampling method. Slovin's formula was used to collect a research sample of 30 respondents. The results showed that a number of respondents took good care of the perineal wound (27 respondents, 90 percent), did not abstain from food (25 respondents, 83 percent), maintained good personal hygiene (29 respondents, 96 percent), and the perineal wound healed well (24 respondents, 80 percent). Fisher's Exact test results showed perineal wound care had a relationship with perineal wound healing time with a p-value of 0.005 < 0.05; abstinence from food had a relationship with perineal wound healing time with a p-value of 0.000 < 0.05; and personal hygiene had no relationship with perineal wound healing time with a p-value of 0.200.